Rancang Bangun Sistem Deteksi Kebakaran pada Ruangan Berbasis Internet of Things (IoT) - Sari Suhartini; Mardian Peslinof; Muhammad Ficky Afrianto (Universitas Indraprasta PGRI Jakarta, 2023)
Indoor fire is usually contained by calling the fire department. However, firefighters sometimes arrive at the location when the fire burns. Room safety usually only uses APAR and has not implemented a detection system to detect fire. Therefore, a system is needed to minimize the fire. The research is conducted to design and manufacture an Internet of Things (IoT)-based indoor fire detection system and to look at the characteristics of the system using methods of problem analysis, design, system assembly, characteristic test and test data analysis. The system consists of smartphone monitoring and alert by utilizing IR flame, MQ-2 and MLX90614 sensors to detect fire indications and of NodeMCU ESP8266 as a microcontroller. The results obtained are an average error of 1.04% and accuracy of 98.92% on temperature readings, an average system precision of 93% on smoke readings and 98.8% on temperature readings. The warning received on the smartphone is less than 2 seconds. Monitoring results in the Electronics, Robotics and Automation Laboratory room do not detect any indication of fire.